Mechanical and Ballistic Characterization of Armour Steel Plate against 0.30-Calibre APM2 Armour Piercing Projectile - Sanusi, O.M.; Akindapo, J.O.; Dauda, M.; Bello, Y; Olaleke, M.O. (Ife Journal of Technology, 2016)
An experimental analysis of SAN-armour steel plate subjected to high velocity impact of 0.30 calibre armour piercing projectiles is presented. The hardness and impact strength of the plate were assessed following standard procedures; while microstructural examination was carried out on etched sample of the plate. The ballistic performance of the 6 mm thick steel was examined, to obtain an estimate for the V50 ballistic test for armour steel plate, impacting projectiles at 30° obliquity to the target plate from 20 m range. The observed performance was compared with the requirements ofMIL-STD-46100E standards. The results showed that the specimen tested has a tensile strength of 1290MPa, hardness value of 483HBN, 10.1% elongation, impact resistance value of 27J, and that the morphology of the original microstructure has martensitic/bainitic matrix. The ballistic performance of the plate agreed with the minimum ballistic requirements of MIL-STD-46100E standards. This study, therefore established that the SANarmour steel plate is effective for anti-ballistic applications.